2016
DOI: 10.1016/j.envpol.2016.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Soil respiration contributes substantially to urban carbon fluxes in the greater Boston area

Abstract: Urban areas are the dominant source of U.S. fossil fuel carbon dioxide (FFCO2) emissions. In the absence of binding international treaties or decisive U.S. federal policy for greenhouse gas regulation, cities have also become leaders in greenhouse gas reduction efforts through climate action plans. These plans focus on anthropogenic carbon flows only, however, ignoring a potentially substantial contribution to atmospheric carbon dioxide (CO2) concentrations from biological respiration. Our aim was to measure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
5
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 40 publications
5
63
5
2
Order By: Relevance
“…The average fluxes of CO 2 -C and N 2 O-N in this study are lower than average fluxes measured from fertilized urban lawns and turf and mulched garden beds [67,68], but greater than in native grasslands and wheat fields that received no irrigation and fertilization ( [69]; Figure 5). Average CO 2 -C fluxes observed in this study are lower than fluxes reported by Decina [56] from urban lawn and landscaped sites, but greater than average fluxes from urban [56] and rural forests [70] (Figure 5). For N 2 O-N, our average and range of fluxes were much smaller than the range of fluxes (30 to 900 µg m −2 h −1 ) observed from fertilized corn fields ([71]; Figure 5).…”
Section: Comparison Of Bioretention Fluxes To Other Landscapescontrasting
confidence: 47%
See 2 more Smart Citations
“…The average fluxes of CO 2 -C and N 2 O-N in this study are lower than average fluxes measured from fertilized urban lawns and turf and mulched garden beds [67,68], but greater than in native grasslands and wheat fields that received no irrigation and fertilization ( [69]; Figure 5). Average CO 2 -C fluxes observed in this study are lower than fluxes reported by Decina [56] from urban lawn and landscaped sites, but greater than average fluxes from urban [56] and rural forests [70] (Figure 5). For N 2 O-N, our average and range of fluxes were much smaller than the range of fluxes (30 to 900 µg m −2 h −1 ) observed from fertilized corn fields ([71]; Figure 5).…”
Section: Comparison Of Bioretention Fluxes To Other Landscapescontrasting
confidence: 47%
“…For both gases, temperature was positively correlated with gas fluxes. Various other environmental factors besides soil temperature and water content, and NH 4 + -N and NO 3 − -N concentrations regulate gas fluxes such as the amount of OM, mineralizable carbon, and microbial biomass [55][56][57], which are relevant to various stormwater control structures. Decina [56] observed significant and positive correlation of soil CO 2 efflux with soil organic matter concentration, soil C:N ratio and the depth of the leaf litter layer.…”
Section: Environmental Effects On Fluxesmentioning
confidence: 99%
See 1 more Smart Citation
“…The research community is aware of the potential for soil/vegetation respiration outside the growing season to contribute to observed CO 2 mixing ratios, but empirical evidence in the urban domain has been limited. Only recently have there been measurements within mid-latitude urban areas to support the notion that the flux may be large enough to warrant explicit inclusion (Decina et al, 2016;Kaye et al, 2005;Chen et al, 2014). Indeed, the soil/vegetation covered landscape within the urban domain tends to be heavily managed with both water and soil nutrients available throughout the year (Kaye et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We draw from three studies that measured urban respiration fluxes in U.S. cities at times of the year coincident with the September-April period of the INFLUX inversion (Decina et al, 2016;Kaye et al, 2005;Chen et al, 2014). The three studies performed measurements in Boston MA, Fort Collins CO, and Baltimore MD.…”
Section: Animal Respirationmentioning
confidence: 99%